1958
DOI: 10.1139/b58-012
|View full text |Cite
|
Sign up to set email alerts
|

The Peach Replant Problem in Ontario: Vi. The Relation of Pratylenchus Penetrans to the Growth of Young Peach Trees

Abstract: Further evidence was accumulated indicating that the peach replant disease decreases in severity as the interval increases in time between removal of the old orchard and the planting of new trees. The ameliorating effect of the interval may be related to the decline of Pratylenchus penetrans (Cobb, 1917) Sher & Allen, 1953. In experiments, increased growth of peach was associated with the control of P. penetrans by nematocides and P. penelrans was found to be the first nematode to attack newly developing p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
8
0

Year Published

1960
1960
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 1 publication
2
8
0
Order By: Relevance
“…However, causes for peach replant prob lems have been studied from many different points of view such as nematodes (15,16,17), fungi (22, 23) and allelopathins (6,8,10,13,14,18,19,20). Therefore, it seems most reasonable that while in some cases a certain single factor may be predominant, in other cases other factors may complicate the problems.…”
Section: Resultsmentioning
confidence: 99%
“…However, causes for peach replant prob lems have been studied from many different points of view such as nematodes (15,16,17), fungi (22, 23) and allelopathins (6,8,10,13,14,18,19,20). Therefore, it seems most reasonable that while in some cases a certain single factor may be predominant, in other cases other factors may complicate the problems.…”
Section: Resultsmentioning
confidence: 99%
“…Economically effective pesticides have been in use since the mid 1940s (Mai & Abawi 1981). Early success with soil fumigants, such as ethylene dibromide, chlorobromopropene, dichloropropane-dichloropropene mixtures, and methyl bromide, strongly supported the contention (Koch 1955) that nematodes were a major factor in replant problems of old orchard sites in Ontario (McBeth 1954, Mountain & Boyce 1958b, Wensley 1956). Now, preplant chemical treatment of nursery or orchard soils before replanting is a standard recommendation if high levels of nematodes are detected (Bird 1968, Townshend 1974, Mai & Abawi 1981.…”
Section: Nonspecific Replant Diseasesmentioning
confidence: 99%
“…Other studies (Mountain & Boyce 1958b) indicated that linear growth of peach seedlings was reduced 50% by replant disease caused by rootlesion nematodes. By treating plots with broadspectrum biocides (methyl bromide) growth was increased by 70%.…”
mentioning
confidence: 97%
“…The root-f esion nematode (Pratylenchus penetrans Cobb), which is widespread in the Niagara Peninsula (Potter and Townshend 1973), has caused the loss of peach trees (Prunus persica (L.) Batsch) in new and replacement orchards and contributed to a decline in vigor in established orchards (Mountain and Boyce 1958b;Mountain and Patrick 1959;Bird 1969; Allen and Marks 1977). The pin nematode (Prtratylenchus projectus Jenkins), which is also present in large numbers in Niagara peach orchards (Mountain and Boyce 1958a;Townshend et al 1984), is suspected of affecting the longevity and productivity of established peach orchards (Mountain and Boyce 1958b) and…”
mentioning
confidence: 99%
“…In commercial peach nurseries. which used to be lo0% infested with P. penetrans (Mountain and Boyce 1958b), fumigation has become standard practice. Similarly, over 75% of all peach orchards to be planted or replanted are now fumigated.…”
mentioning
confidence: 99%